PENGARUH MEDIA STORIGAMI TERHADAP KETERAMPILAN MENYIMAK CERITA FIKSI SISWA KELAS IV DI SD NEGERI 79 PALEMBANG - Eva Elyehon Silalahi; Destiniar; Putri Dewi Nurhasana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of using story-based media on the listening skills of fourth grade students at SDN 79 Palembang. This type of research uses a quantitative approach with a quasi-experimental method and a posttest control group design research design. The population of this study were fourth grade students at SDN 79 Palembang. Samples were taken using a purposive sampling technique using two classes as the experimental group and the control group. The data collection technique in this study is using a test instrument. The data analysis technique was processed by testing the parametric independent samples t-test or t-test with the help of SPSS 25 software. Data analysis showed the sig. (2-tailed) 0.003 <0.05 which means that there is a difference in the average posttest scores in the control class and the experimental class. Based on the results of the t-test analysis, it shows t-count = 3,150 > t-table = 2,000 which means Ho is rejected. So it can be concluded that there is an effect of the use of storytelling media on the skills of listening to fictional stories of fourth grade students at SDN 79 Palembang